Antioxidant and Antibactery Activity of Ethanol Extract of Selutui Puka Leaves (Tabernaemontana macrocarpa Jack.) Against Propionibacterium acnes - Handayani, Fitri; Fatimah, Nurul; Ansyori, Achmad Kadri; Sari, Putri Eka; Agustina, Ika (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2024)
The selutui puka plant (Tabernaemontana macrocarpa Jack.) is a plant that has many benefits for the Dayak community in the West Kutai area, Karangan Village, Mook Manaar Bulatn District, East Kalimantan. Empirically, the Dayak tribe uses selutui puka to treat cancer, herpes, scabies, itchy skin, acne and blisters. Metabolites contained in selutui puka leaves such as alkaloids, flavonoids, tannins, saponins, and steroids have potential as antioxidants and antibacterials. Selutui puka leaf can be used as an alternative to natural acne treatment, because it is known that the use of natural ingredients has lower side effects. The purpose of this study was to determine the antioxidant and antibacterial activity of the ethanol extract of selutui puka leaves against Propionibacterium acnes. This research was conducted by experimental method. The research sample was selutui puka leaf. The research phase includes sample preparation, plant determination, simplicia manufacture, extraction, testing of antioxidant activity using UV/VIS Spectrophotometer at extract concentrations of 300 ppm, 325 ppm, 350 ppm, 375 ppm and 400 ppm. Quercetin as a positive control and comparison. The antibacterial activity test consisted of making media, culturing Propionibacterium acnes, and testing antibacterial activity using the disc diffusion method at extract concentrations of 5%, 10%, and 15%. Data were analyzed descriptively. The data from the results of this study are presented in the form of tables and figures. IC50 of ethanol extract of selutui puka leaves was 333.60 ppm with very weak category. The diameter of the inhibition zone of the ethanolic extract of selutui puka leaves against Propionibacterium acnes was 7.81 mm (5%), 7.44 mm (10%) and 8.63 mm (15%) in the medium category.